Aplicación de estrategias didácticas para desarrollar la inteligencia kinestésica y musical en los niños de la escuela de educación básica Ing. Jorge Alex Serrano del cantón El Guabo, provincia de El Oro, periodo 2014 – 2015. - Armijos Correa, Marjorie Paola (2015)
The Thesis entitled, TEACHING STRATEGIES FOR DEVELOPING APPLICATION INTELLIGENCE AND MUSICAL kinesthetic IN CHILDREN OF BASIC EDUCATION SCHOOL ING. ALEX JORGE SERRANO CANTON THE GUABO, PROVINCE OF GOLD, PERIOD 2014 - 2015, the study is important because it will allow to analyze the influence of the development of leisure to improve gross motor skills in the teaching-learning process activities.